(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Indiais among the most potential developing economics in the world. Why do we callit as a potential economy? The simple reason being the growth rate of economy.Standing shoulder to shoulder with strong neighbor China, India is progressingwith growth rate in the range of 6 to 7 % consistently, India was even consideras one of those most fortunate countries which bore the burns of globalrecession the least. The supporting factor for this is fiscal policies ofIndian Govt. And the backbone of this strong potential and the most competenteconomy is agriculture.